Actel: Standardised analysis of acoustic telemetry data from animals moving through receiver arrays. Issue 1 (8th November 2020) - Flávio, Hugo; Baktoft, Henrik
Abstract: Acoustic telemetry data often contain erroneous detections, which need to be addressed before further analysis. It is important that this process is systematic, standardised and reproducible. The r package actel provides a systematic conditional pipeline to filter and analyse acoustic telemetry data in a reproducible fashion, for animals moving between receiver arrays. actel outputs a standardised report containing the main results and the steps taken by the user, in addition to summary information for each animal and other content such as efficiency estimations for each receiver array. actel improves the reproducibility of the acoustic data filtering and analysis, and simplifies the integration of acoustic data sets originating from different studies (in time and/or in space).